PERFORMANCE OF GUIDANCE COUNSELING TEACHERS ACCORDING TO STUDENT PERCEPTIONS AT SMPN 19 MEDAN - Widya Lestari, Utami (Faculty of Tarbiyah nad Teacher Training, 2023)
This research aims to find out and analyze how description of the performance of guidance and counseling teachers according to student perceptions at SMPN 19 Medan Academic Year 2022/2023. This research uses an approach The research is descriptive qualitative. Number of sample members in this study namely, as many as 10 grade 8 students from SMP Negeri 19 Medan. Data collection can be done directly by the research subjects with observation, interviews, and documentation. Data analysis techniques with data reduction, data presentation, and drawing conclusions while techniques validity of using data triangulation. Based on research conducted by researchers, it is known that teacher performance counseling guidance according to students' perceptions at SMP Negeri 19 Medan, namely BK teachers in providing services are very helpful in overcoming student problems, the student can ask for help from the guidance and counseling teacher in overcome the problems experienced by these students. Then the guidance and counseling teacher in its performance it provides real implementation in everyday life. The results of this research show that the performance of guidance and counseling teachers in junior high schools Negeri 19 Medan has been said to be quite good at being responsible carry out their duties, their performance becomes a role model, deeply creative providing services, implementing attractive services, and their performance optimally so that student problems can be resolved well through guidance the counseling.